Epidural analgesia during surgery and its relation to postoperative myocardial infarction: meta-analysis - Qiong Hu; Xuqi Yu; Ting Zhou (Videosurgery and Other Miniinvasive Techniques)
Introduction: Epidural analgesia has been studied for its potential advantages after surgery in a number of random ized clinical trials, with most finding improvements in pain and secondary endpoints like the incidence of postoper ative complications. Aim: To assess the relationship between use of epidural analgesia and adverse cardiac outcomes expressed by myo cardial infarction (MI). Material and methods: Fifty-three studies were recruited to quantify the influence of different surgical-related anal gesic methods on clinical parameters (mortality and adverse events). The results of these trials were analysed using a random effects model, which was then used to calculate the mean difference (MD) with 95 per cent confidence intervals (CIs). Results: Epidural analgesia resulted in preferred cardiac outcomes compared with traditional analgesia. These find ings were supported by significantly lower MI events for the epidural analgesia group as follows: p = 0.005, p = 0,007, and p = 0.03 for the total number of included studies, studies with high risk of bias, and studies with low risk of bias, respectively. Studies with intermediate risk showed a non-significant difference between both groups (p = 0.7). Conclusions: Epidural analgesia has a significant protective cardiac effect through the reduction of postoperative MI events among surgery subjects.